Localization of Certain Histochemical Entities in the Caput Epididymis of Assam - Sarma, Kamal; Kalita, S N; Devi, J (Indian Journal of Veterinary Anatomy, 2012)
The present study was conducted on epididymis of male Assam goats. The stereo-cilia and the luminal contents of the epididymal tubules showed a weak to moderate reaction for basic proteins from 4th month of age onwards. The basement membrane of the tubules was moderately reactive to glycogen in all the age groups except in day-old kids. The tubular epithelium exhibited a weak reaction for acidic mucopolysaccharides in the kids from birth to 4th month of age, and moderate reaction from 6th month of age onwards.